1987
DOI: 10.1159/000128684
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Aminated Glucan in Experimental Endogenous Peritonitis

Abstract: The effect of prophylactic intraperitoneal aminated glucan on the survival rate and formation of adhesions and abscesses was investigated in rats with acute and subacute peritonitis, respectively induced by cecal perforation and ileal ligation. A significantly reduced mortality was found in both forms of peritonitis. Pretreatment by aminated glucan also significantly reduced the number of abscesses and peritoneal adhesions. An about threefold increase in peritoneal macrophages in aminated glucan-treated rats c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The situation becomes un controllable by surgical procedures such as: puncture or perforation of an intestinal sec tion, intestinal elimination or blood flow in terruption, the exclusive interruption of blood supply to a part of the intestine, cecal ligature with or without puncture [7][8][9][10][11][12][13][14][15][16]. The amount of feces escaping into the abdo men is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The situation becomes un controllable by surgical procedures such as: puncture or perforation of an intestinal sec tion, intestinal elimination or blood flow in terruption, the exclusive interruption of blood supply to a part of the intestine, cecal ligature with or without puncture [7][8][9][10][11][12][13][14][15][16]. The amount of feces escaping into the abdo men is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The agent is administered intraperitoneally. It has been shown by an American group [35] and by us [36] that it effectively protects against intraabdominal sepsis. Furthermore, we have recently demonstrated that glucan has antiadhesive properties which cannot be related to its preventive qualities against in fection [37], Its mechanism of action in this respect is probably similar to that of dextran.…”
Section: Attempts To Prevent Adhesionsmentioning
confidence: 99%
“…Studying 42 different glycans, Seljelid et al [22] found that the polyglucose [31-3 D-glucan had the strongest stimulatory effect on macrophages. We have shown recently that a semisoluble aminated derivative of this compound protected against diverse types of peritonitis [1,3]. However, the long-term prophylactic and pharmacodynamic effects of intraperitoneal semisoluble aminated glucan (SAG) on septic peritonitis has not been evaluated, and this was therefore the first objective of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…These facts have stimulated studies of the possibility to enhance non-specific host responses to postoperative infection. Accumulated evidence are now available demonstrating that high-molecular weight carbohydrates (glycans) stimulate immune reactions both in vitro [21,22] and in vivo [1,23,26]. Studying 42 different glycans, Seljelid et al [22] found that the polyglucose [31-3 D-glucan had the strongest stimulatory effect on macrophages.…”
Section: Introductionmentioning
confidence: 99%